Analysis Of Risk Factors Affecting Hypertension Disease In The Jayaloka Village Area, Empat Lawang Regency - Agustina, Elvira Eka; Andriani , Melda; Wulandari, Suci; Kartini, Aprilia; Sari , Winda Puspa; Aprianti, Delta; Rohani, Tuti; az, Danur (Jurnal Pengabdian Mandiri, 2025)
Hypertension, or high blood pressure, is one of the leading causes of death and disability worldwide. This disease has become a growing global health problem, especially in developing countries, including Indonesia. Hypertension often shows no symptoms in its early stages, earning it the nickname "silent killer." This study aims to identify the main risk factors contributing to hypertension in urban communities and evaluate strategies for its management.This research employed a quantitative approach with a cross-sectional study design, involving respondents aged 30-65 years residing in the Jayaloka subdistrict. Data were collected through structured interviews and blood pressure measurements using a digital sphygmomanometer. Statistical analysis was conducted to determine the relationship between risk factors such as smoking habits, excessive salt consumption, lack of physical activity, obesity, and family history of hypertension.The results showed that 40% of respondents experienced hypertension, with a higher prevalence in the age group above 50 years. The main risk factors significantly associated with hypertension were obesity (p < 0.05), high salt consumption (p < 0.05), and a family history of hypertension (p < 0.01). Management strategies involving lifestyle modifications such as a low-salt diet, increased physical activity, and health education proved effective in reducing blood pressure among individuals with mild to moderate hypertension. This study concludes that hypertension can be prevented and managed through a combination of promotive and preventive efforts. Therefore, community health interventions focusing on controlling major risk factors are essential to reduce the burden of hypertension in the Jayaloka subdistrict